The Power of Readiness Theory and the Success of Inter-Governmental Authority on Development (IGAD) Peace Process in South Sudan - KULANG, Timothy Tut (Advances in Social Sciences Research Journal, 2019)
In this article, the South Sudan conflict will be analyzed by examining the IGAD mediation process between the Government of South Sudan and the Sudan People’s Liberation Movement/Army in Opposition (SPLM/A IO). The study will look into factors that prompted the IGAD states to call for an emergency meeting and initiate peace talk just few days after the outbreak of the conflict in December 2013. The study will use the Readiness Theory to examine the factors that pushed the parties to the negotiation table and enable the IGAD to succeed or failed. Although the mediation was somehow shaky characterized with mistrust and suspicion among the parties, The IGAD mediators was also questionable since some of the IGAD states were already perceived has taken part in one way or other. The study will explore two major factors; first the factor that led to the agreement between the parties and the second one will be looking into assumption of readiness theory applicable to this case study. In conclusion, the study will investigate the level of mistrust and suspicion which was very high through out the negotiation and almost failed the talk to the level of parties being coerced to sign an agreement against their will of which government presented number of reservations to the mediator and went unaddressed will in many observers’ opinion was the cause of the July 2016 J1 dog-fight. But the IGAD continue pd pushing for peaceful settlement of the conflict and initiated handshake and face-to-face meetings between the leaders which eventually resulted into the Khartoum revitalized agreement in September 2018. Other arrangements also followed such as the spiritual retreat in Vatican in April 2019, which was attended by almost all leaders, but despite all these, still the motivation is in question and the time will prove this wrong.